ANALISIS NILAI KEJUJURAN TOKOH “NUSSA” DALAM ANIMASI NUSSA DAN RARA AYU - Ayu Nuriyah Syibly; Taopik Rahman; Aini Loita (Jurnal Binagogik, 2024)
This study aims to analyze the value of honesty in Nussa's characters in animations of Nussa and Rara.The type of research used is a qualitative approach with methods of content analysis. (content analylis).The results of research are known that Nussa and Rara's animations greatly give character values, oneof which is the value of honesty. Nussa's character has an honest personality, this is shown in thedialogue episode "learn to be honest" Nussa talks after learning that Abdul his friend is not honest indoing his job, so Nussa advised that honesty calms the heart and Nussa has done his job honestly andgot a score of 95. The episode "Take No Yes?" shows that Nussa tries to be honest when she finds moneywith Rara and waits for her owner to take it. And the episode "Learn to Sell", Nussa has an honestattitude shown in her brother's cheating when there is no return of money so that the money doesn'tneed to be returned. So Nussa advised Rara remembering the advice of Umma that we should overseethe trade nature of the Messenger, that is, Trust, honest, and trustworthy. From these three episodes itcan be concluded that Nussa has a high value of honesty, thanks to the advice that he always rememberedthat honesty calms our hearts.